In situ synthesis and electrochemical performance of MoO3−x nanobelts as anode materials for lithium-ion batteries. Issue 34 (16th August 2019) - Wu, Qi-Long; Zhao, Shi-Xi; Yu, Le; Yu, Lü-Qiang; Zheng, Xiao-Xiao; Wei, Guodan
Abstract : MoO3− x nanobelts with different concentrations of oxygen vacancies were synthesized in situ, whose effects on lithium-ion storage performance were researched. Abstract : MoO3− x nanobelts with different concentrations of oxygen vacancies were synthesized by a one-step hydrothermal process. XPS test results show that oxygen vacancies are distributed from the exterior to the interior of the MoO3− x nanobelts. As an anode material for lithium-ion batteries, MoO3− x -10 releases excellent rate capacitance. It can maintain a high specific capacitance of about 500 mA h·g −1 at a high current density of 1000 mA·g −1 . In the aspect of cycling stability, MoO3− x -10 can retain a high specific capacity of 641 mA h·g −1 after cycling for 50 times at 100 mA·g −1 and 420 mA h·g −1 after cycling for 100 times at 500 mA·g −1 . The coexistence of oxygen vacancies and low-valence Mo ions is conducive to the intercalation/de-intercalation of Li ions and to promoting redox reactions. It has been proved to be a significantly effective way in which oxygen vacancies can improve the integrated performance of MoO3− x nanobelts as anode materials.